Theory and Applications of Web 3.0 in the Media Sector - Veglis, Andreas; Dimoulas, Charalampos (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This volume is a reprint of the Special Issue "Theory and Application of Web 3.0 in the Media Sector". Launched to highlight vital multidisciplinary perspectives, the SI's contents are both theory- and application-oriented. The advancements of computational processing and storage capacities (at affordable or decreasing costs), the evolution of content compression techniques, and the constant update of networking infrastructures led to the domination of the so-called User-Generated Content (UGC). The proliferation of mobile devices, offering inherent networking with enhanced content capturing and sharing capabilities, also fueling the models of Participatory and Citizens' Journalism. Thus, the interest has shifted to semantic services, purposing, among others, to automate content production, publishing, validation, documentation, and management. Such technological solutions have already entered the media sector, with their successful growth and elaboration requiring multidisciplinary effort supported by digital literacy initiatives. Nevertheless, further research is needed for the transition to the new media era in which algorithmic automations and semantic services will serve their original purposes, helping both media professionals and broader audiences. A total of 11 contributions were published within this volume, enlightening various aspects of contemporary Web 3.0 services from both technological/algorithmic and conceptual/social science approaches..